Sufentanil inhibits the proliferation and epithelial mesenchymal transition of lung cancer cells through Wnt/beta-catenin signaling pathway. Issue 4 (1st April 2022) - Guan, Minghan; Huang, Yifeng; Lin, Xiaowen
ABSTRACT: Lung cancer is the most common malignancy and leading cause of cancer-related death. Sufentanil is a commonly used opioid anesthetic in clinics. This study aimed to explore the effects of sufentanil on the malignant behavior of lung cancer cells. H460 and H1299 lung cancer cell lines were selected for in vitro experiments. The MTT assay was conducted to detect cell viability. Proliferation ability was determined by colony formation and EdU assays. Transwell assays were performed to measure migration and invasion abilities. Western blotting was used to detect the expression of related proteins. LiCl was used to activate the Wnt/β-catenin signaling pathway. Sufentanil decreased the proliferation, migration, and invasion of H460 and H1299 cells. The protein expression levels of vimentin, N-cadherin, β-catenin, c-Myc, and MMP2 were downregulated, while those of E-cadherin and ZO-1 were upregulated after sufentanil treatment. LiCl treatment reversed the effects of sufentanil on H460 and H1299 cells. Sufentanil inhibited the proliferation, migration, invasion, and epithelial–mesenchymal transition of lung cancer cells by regulating the Wnt/β-catenin signaling pathway. Graphical abstract: uf0001